Impacts of Fc[gamma]RIIB and Fc[gamma]RIIIA gene polymorphisms on systemic lupus erythematous disease activity index - Karimifar, Mansoor; Akbari, Khosro; ArefNezhad, Reza; Fathi, Farshid; Moosaeepour, Mohammad; Motedayyen, Hossein (BMC research notes, 2021)
Systemic lupus erythematous (SLE) disease is a chronic autoimmune disease with unknown etiology that can involve different organs. Polymorphisms in Fc[gamma] receptors have been identified as genetic factors in susceptibility to SLE. This study was aimed to investigate effects of two single nucleotide polymorphisms (SNPs) within Fc[gamma]RIIB and Fc[gamma]RIIIA genes on systemic lupus erythematous disease activity index (SLEDAI) in an Iranian population. Our findings indicated TT and GG genotypes were the common genotypes of Fc[gamma]RIIB and Fc[gamma]RIIIA SNPs in SLE patients, respectively. There were no significant differences in genotype and allele frequencies of Fc[gamma]RIIB and Fc[gamma]RIIIA SNPs in SLE and healthy subjects. However, the frequencies of genotypes and alleles of Fc[gamma]RIIB and Fc[gamma]RIIIA SNPs were significantly associated with some clinical manifestations used to determine SLEDAI (P < 0.001-0.5).